UNSCRIPTED DRAMA: SOCCER AUDIENCE RESPONSE TO SUSPENSE, SURPRISE, AND SHOCK. (17th December 2019) - Buraimo, Babatunde; Forrest, David; McHale, Ian G.; Tena, J.D.
Abstract : By modeling minute‐by‐minute television audience figures from English Premier League soccer matches, with close to 50, 000 minute‐observations, we show that demand is partly driven by suspense and surprise. We also identify an additional relevant factor of appeal to audiences, namely shock, which refers to the difference between pre‐match and current game outcome probabilities. Suspense, surprise, and shock remain significant in the presence of a traditional measure of outcome uncertainty. ( JEL C23, D12, L82, L83, Z20)